Highly Strained Nanoscale Bicyclophane Monolayers Entering the Third Dimension: A Combined Synthetic and Scanning Tunneling Microscopy Investigation. Issue 6 (6th May 2021) - Henzel, Sebastian; Becker, Steven; Hennen, Daniel; Keller, Tristan J.; Bahr, Joshua; Jester, Stefan‐S.; Höger, Sigurd
Abstract: Invited for this month's cover are the collaborating groups of Prof. Dr. Sigurd Höger and Dr. Stefan‐S. Jester from Rheinische Friedrich‐Wilhelms‐Universität Bonn, Germany. The cover picture shows a bicyclophane that forms a two‐dimensional supramolecular nanopattern on graphite at the solid/liquid interface. After adsorption, the central unit points towards the volume phase. Read the full text of the article at 10.1002/cplu.202000711 . Abstract : "It is always fascinating when a designed molecule has been successfully synthesized, purified, and characterized, and is visualized for the first time by scanning tunneling microscopy. We succeeded in showing that the supramolecular arrangement of the molecules is independent from the respective intraannular substitution within the limits of measurement accuracy." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202000711 ).